Protecting the rights of Palestinian children during the Israeli aggression on the Gaza Strip in 2022 - Elshobake, Mohammed R. M. (2022)
The human rights issue has gained great importance in the twentieth century because of the atrocities that had occurred between countries in the two world wars. Hence, after the Second World War, the countries have convened many international conventions regarding the protection of human rights, and they established many international bodies and organizations for this purpose. International law is concerned with the protection of human rights and fundamental freedoms in times of peace and war. The protection of children's rights is the most important of these rights, which are enshrined in international conventions and treaties. The Palestinian people have been suffering for many years because of the effects of Israeli violations. This suffering afflicts Palestinian children and affects their civil rights and protection in times of war. Israeli Occupation have killed nineteen Palestinian children in the occupied Palestinian territory, taking the death toll since the start of 2022 to 37 children. Seventeen children of whom were killed during the Israeli aggression on the Gaza Strip from 5-7 August 2022. Through doctrinal and legal study and content analysis, this paper analyses the important relevant legal provisions under international humanitarian law and applies these provisions to the situation in the Gaza strip during the Israeli aggression of 2022 to identify Israeli violations against Palestinian children. The findings of the research are expected to contribute to strengthening the protection of Palestinian children from any violation.